Analisis Manajemen Risiko pada Usaha Konveksi Baju Muslim Wanita dalam Upaya Menjaga Stabilitas Operasional - Syahira Rachmadina; Dena Destiani; Listi Sinta Nur Oktaviani; Najla Putri Pramesdianti; Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Risk management is an important element in maintaining business continuity, especially in the garment industry, which faces high pressure in terms of timeliness, production quality, and changing customer needs. The garment industry, which is highly competitive and dependent on timeliness and quality standards, requires the identification and management of risks as a strategic measure to minimize potential disruptions. This study uses a qualitative approach through direct interviews with business owners to explore sources of risk, control processes, and the effectiveness of actions that have been taken. The results show that the main risks include delays in raw materials, damage to production machinery, inconsistencies in production quality, and labor factors. Mitigation efforts, including diversification of raw material suppliers, regular machine maintenance, strengthening of production SOPs, quality control systems, and improving employee competence through training, have been proven to help reduce potential losses and maintain smooth production processes. The application of ISO 31000 principles provides direction in sustainable risk management, particularly in the context of faster and more accurate decision-making. Thus, the implementation of structured risk management contributes significantly to operational stability, thereby increasing customer confidence and the competitiveness of garment businesses in the market.